Distinct and Specific Role of NlpC/P60 Endopeptidases LytA and LytB in Cell Elongation and Division of Lactobacillus plantarum - Duchêne, Marie-Clémence; Rolain, Thomas; Knoops, Adrien; Courtin, Pascal; Chapot-Chartier, Marie-Pierre; Dufrêne, Yves F.; Hallet, Bernard F.; Hols, Pascal (Frontiers in Microbiology, 2019)
Peptidoglycan (PG) is an essential lattice of the bacterial cell wall that needs to be continuously remodeled to allow growth. This task is ensured by the concerted action of PG synthases that insert new material in the pre-existing structure and PG hydrolases (PGHs) that cleave the PG meshwork at critical sites for its processing. Contrasting with Bacillus subtilis that contains more than 35 PGHs, Lactobacillus plantarum is a non-sporulating rod-shaped bacterium that is predicted to possess a minimal set of 12 PGHs. Their role in morphogenesis and cell cycle remains mostly unexplored, except for the involvement of the glucosaminidase Acm2 in cell separation and the NlpC/P60 D,L-endopeptidase LytA in cell shape maintenance. Besides LytA, L. plantarum encodes three additional NlpC/P60 endopeptidases (i.e. LytB, LytC and LytD). The in silico analysis of these four endopeptidases suggests that they could have redundant functions based on their modular organization, forming two pairs of paralogous enzymes. In this work, we investigate the role of each Lyt endopeptidase in cell morphogenesis in order to evaluate their distinct or redundant functions, and eventually their synthetic lethality. We show that the paralogous LytC and LytD enzymes are not required for cell shape maintenance, which may indicate an accessory role such as in PG recycling. In contrast, LytA and LytB appear to be key players of the cell cycle. We show here that LytA is required for cell elongation while LytB is involved in the spatio-temporal regulation of cell division. In addition, both PGHs are involved in the proper positioning of the division site. The absence of LytA activity is responsible for the asymmetrical positioning of septa in round cells while the lack of LytB results in a lateral misplacement of division planes in rod-shaped cells. Finally, we show that the co-inactivation of LytA and LytB is synthetically affecting cell growth, which confirms the key roles played by both enzymes in PG remodeling during the cell cycle of L. plantarum. Based on the large distribution of NlpC/P60 endopeptidases in low-GC Gram-positive bacteria, these enzymes are attractive targets for the discovery of novel antimicrobial compounds.